2019
DOI: 10.18267/j.pep.681
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Impact of Firm Size on the Relationship between Working Capital Management and Profitability

Abstract: This study investigates whether firm size moderates the relationship between cash conversion cycle and profitability over 8-year period for 285 German non-financial firms. The moderated regression results reveal that the relationship between cash conversion cycle and profitability is moderated by firm size. As the firm size gets smaller and the cash conversion cycle gets longer, the returns on assets decreases. When the firm size gets bigger and the cash conversion cycle gets longer, on the other hand, the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 49 publications
2
36
1
1
Order By: Relevance
“…In light of this threat, businesses may focus on the areas under their control, covering working capital. The third motivation behind this paper is the fact that a large body of recent research studies has investigated the impact of working capital on corporate performance from the perspective of developed economies especially the US, the UK, and China (i.e., Dalci et al 2019;Ren et al 2019;Laghari and Chengang 2019;Mahmood et al 2019;Goncalves et al 2018;Tsuruta 2018;Aktas et al 2015;Mun and Jang 2015;Enqvist et al 2014;Baños-Caballero et al 2014). Specifically, a small number of studies have focused on emerging economies: Uganda (Kabuye et al 2019), Egypt (Moussa 2018), Vietnam (Le 2019;Nguyen and Nguyen 2018), Malaysia (Yusoff et al 2018), high-growth firms from emerging Europe (Bot , oc and Anton 2017), Pakistan (Habib and Huang 2016), Ghana (Amponsah-Kwatiah and Asiamah 2020), Egypt, Kenya, Nigeria, and South Africa (Ukaegbu 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In light of this threat, businesses may focus on the areas under their control, covering working capital. The third motivation behind this paper is the fact that a large body of recent research studies has investigated the impact of working capital on corporate performance from the perspective of developed economies especially the US, the UK, and China (i.e., Dalci et al 2019;Ren et al 2019;Laghari and Chengang 2019;Mahmood et al 2019;Goncalves et al 2018;Tsuruta 2018;Aktas et al 2015;Mun and Jang 2015;Enqvist et al 2014;Baños-Caballero et al 2014). Specifically, a small number of studies have focused on emerging economies: Uganda (Kabuye et al 2019), Egypt (Moussa 2018), Vietnam (Le 2019;Nguyen and Nguyen 2018), Malaysia (Yusoff et al 2018), high-growth firms from emerging Europe (Bot , oc and Anton 2017), Pakistan (Habib and Huang 2016), Ghana (Amponsah-Kwatiah and Asiamah 2020), Egypt, Kenya, Nigeria, and South Africa (Ukaegbu 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some research indicates conflicting conclusions on the relationship between CCC and gross profit could be due to the business's dealing with the exchange rate. In such situations, it is expected that the exchange rate can moderate the CCC and the gross profit association; the resulting hypothesis is then implemented (Dalci et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results revealed that profitability of the firm is significantly affected by the working capital management and working management policies. Dalci et al [2019] investigated whether a firm size moderates the relationship between the cash conversion cycle and profitability for German non-financial firms. The results show that the relationship between the cash conversion cycle and profitability is moderated by a firm size.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Dash and Hauman [2009] proposed a goal programming model for optimizing the working capital management. Dalci et al [2019] investigated whether a firm size influences the relationship between the cash conversion cycle and profitability. Mahmood et al [2019] evaluated the moderating effects of a firm size and leverage on working capital-profitability relationship, presenting how the break-even point shifts when a company expands.…”
Section: Introductionmentioning
confidence: 99%